HUBUNGAN TINGKAT KEPOSITIFAN BTA DENGAN JUMLAH TROMBOSIT PADA PASIEN TB - Poppy Putri Kusumaning Ayu (FKU 15 UMY 556, 2015)
*556 today. Program Directly Observed Treatment Shortcourse (DOTS) has been recommended by WHO as a strategy for detection and cure of TB patients, especially for new sputum smear-positive pulmonary TB case. Acid Fast Bacillus positivity level can act as a marker of the infectious degree whereas the hematological changes can act as a marker for the diagnosis, prognosis and response to therapy of TB disease. Thrombocytosis be the one most common hematologic changes found in TB especially during bacterial infection and can be related with severity of the infection. This study is required to know the relation of AFB sputum-smear positivity levels with the platelet counts in TB patients. Methods: The research was performed by using observational analytic design with cross sectional approach. The sample of this research were 38 TB patients aged 15-50 years old who has been done sputum examination and complete blood count at PKU Muhammadiyah Yogyakarta Unit 1 Hospital. This study data analysis using Spearman correlation test method. Result: The prevalence TB in men was higher than women (74%: 26%). TB patients with AFB 1+ is 10 people (26%), AFB +2 is 13 people (34%) and the AFB +3 is 15 people (40%). The Spearman analysis result show that there is significantly relations between AFB positivity level and platelet level (p<0,05). TB patients with +1 AFB who has low platelet levels is 1 people, who has normal platelet levels is 8 people while has high platelet levels is 1 people. TB patients with 2+ AFB who has low platelet levels is 1 people, who has normal platelet levels is 6 people while has high platelet levels is 6 people. TB Patients with 3+ AFB who has normal platelet levels is 3 people, who has high platelet levels is 12 people and no one has low platelet levels. Conclusions : TB patients with positive AFB sputum-smear mostly has high platelet counts. AFB sputum-smear positivity rate is associated with increased of platelet counts in TB patients. Keywords: AFB positivity levels, platelet, tuberculosis.